Analisa Modal Kerja Terhadap Kinerja Keuangan PT. Kurniawan Transport - Mohd Idris Dalimunthe (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
The ability of working capital to support financial performance is important. Efficient and effective allocation of funds can improve financial performance so as to increase working capital. The purpose of this study was to determine the analysis of working capital management on financial performance at PT. Kurniawan Transport. This research use desciptive qualitative approach,. The subject of this research is PT. Kurniawan Transport and the object of this research is the report on working capital and financial performance at PT. Kurniawan Transport for 3 years, namely 2018-2020. Based on the results of the study, it can be concluded that PT Kurniawan Transport can meet working capital in an effort to improve financial performance. However, in an effort to allocate funds for additional assets in an effort to develop business, it cannot improve financial performance. So that it suffers a loss in the second period which means reduced working capital in that period.